2014
DOI: 10.1111/pai.12311
|View full text |Cite
|
Sign up to set email alerts
|

Non‐digestible oligosaccharides modulate intestinal immune activation and suppress cow's milk allergic symptoms

Abstract: Dietary supplementation with scGOS/lcFOS or scGOS/lcFOS/pAOS during sensitization, both effectively reduce allergic symptoms but differentially affect mucosal immune activation in whey-sensitized mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 40 publications
(68 reference statements)
4
36
2
Order By: Relevance
“…Some studies have suggested that the increase in intestinal IgA could be the mechanism of action of FM (26) , but our results do not agree with that suggestion because intestinal IgA levels in the FM group were similar to those found in the RV group. On the other hand, the GFA diet's results suggest an enhancement in the early response as shown in intestinal IgA, which agrees with other studies showing that GFA activated the immune response (17)(18)(19)(20)(21) , and allows us to hypothesise that these antibodies may solve the infection rapidly, with fewer antibodies needed later on. This early increase in intestinal anti-RV IgA synthesis seems to have been enough to fight against the virus.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have suggested that the increase in intestinal IgA could be the mechanism of action of FM (26) , but our results do not agree with that suggestion because intestinal IgA levels in the FM group were similar to those found in the RV group. On the other hand, the GFA diet's results suggest an enhancement in the early response as shown in intestinal IgA, which agrees with other studies showing that GFA activated the immune response (17)(18)(19)(20)(21) , and allows us to hypothesise that these antibodies may solve the infection rapidly, with fewer antibodies needed later on. This early increase in intestinal anti-RV IgA synthesis seems to have been enough to fight against the virus.…”
Section: Discussionsupporting
confidence: 90%
“…Unlike a variety of immunotherapy approaches that are frequent topics of immunological research, the specific synbiotic combination of non‐digestible oligosaccharides and B. breve M‐16V that was used in this study does not contain the allergen in any (modified) form or dose, but demonstrated potency to reduce an established allergic response. Similar effects were observed previously in a preventive setting, when dietary intervention was initiated before allergic sensitization .…”
Section: Discussionsupporting
confidence: 85%
“…Most studies have focused on non-starch poly-and oligosaccharides [42,43] and demonstrated beneficial effects in a diversity of diseases, such as Alzheimer, diabetes, inflammatory bowel disease, and cardiovascular disease [44][45][46]. Non-starch polysaccharides, particularly β-glucans have been demonstrated to become directly exposed to and potentiate innate immune cells in the small intestine through direct exposure to cells [47] or, alternatively, reduce unwanted colonic inflammation following microbiotamediated fermentation into short-chain fatty acid [48,49]. These fatty acids could function as bioactive compounds and exert a beneficial action on specific intestinal bacteria linked to anti-inflammatory effects.…”
Section: β-Glucans Stimulate Innate Immune Cellsmentioning
confidence: 99%